2018
DOI: 10.1212/wnl.0000000000004923
|View full text |Cite
|
Sign up to set email alerts
|

Necrosis in anti-SRP + and anti-HMGCR + myopathies

Abstract: These data further corroborate the pathogenic role of anti-SRP and anti-HMGCR autoantibodies in IMNM, highlighting humoral mechanisms as key players in immunity and myofiber necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
94
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(108 citation statements)
references
References 29 publications
9
94
1
4
Order By: Relevance
“…Indeed, even if the subacute onset (<6 months) was noted for most of the patients, 33% of patients had a slow progressive muscular deficit ranging from 10 months to several years (three cases had been considered to be MD for more than 10 years prior to the detection of the anti-HMGCR antibodies). 4 The slow progression was also observed in a previous report of an anti-SRP antibodies-related NAM. 8 The co-occurrence of other autoimmune disorders may be found in patients presenting a NAM and could suggest the NAM diagnosis.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Indeed, even if the subacute onset (<6 months) was noted for most of the patients, 33% of patients had a slow progressive muscular deficit ranging from 10 months to several years (three cases had been considered to be MD for more than 10 years prior to the detection of the anti-HMGCR antibodies). 4 The slow progression was also observed in a previous report of an anti-SRP antibodies-related NAM. 8 The co-occurrence of other autoimmune disorders may be found in patients presenting a NAM and could suggest the NAM diagnosis.…”
Section: Discussionsupporting
confidence: 76%
“…In fact, Allenbach et al identified eight autoimmune diseases in the medical history of 5 patients among 45 (thyroiditis in 4 and type 1 diabetes in 1). 4 In our case, the patient developed type 1 diabetes. In a recent cohort of juvenile myositis, 5 out of 440 patients were HMGCR positive and had more frequent joint contractures and arthralgias that may also suggest the diagnosis.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Some experts have argued for the specific utility of rituximab in patients with anti-SRP-antibodies. Recent work has supported the pathogenic role of anti-SRP and anti-HMGCR antibodies in IMNM [144,145], and disease severity has been shown to correlate with antibody titers in anti-SRP myopathy patients [146]. Although a case series suggested that there is a significant reduction in anti-SRP titers after rituximab [147], post hoc analysis from the RIM trial failed to show a significant decrease after rituximab [148].…”
Section: Choice Of Second-line Agentsmentioning
confidence: 99%